On the effectiveness of monetary policy and fiscal policy - Philip Arestis; Malcolm Sawyer (Levy Economics Institute of Bard College, 2003)
Within the framework of macroeconomic policy and theory over the past twenty years or so, a major shift has occurred regarding the relative importance given of monetary policy versus fiscal policy. The former has gained considerably in stature, while the latter is rarely mentioned. Further, monetary policy no longer focuses on attempts to control some monetary aggregate, as it did in the first half of the 1980s, but instead focuses on the setting of interest rates as the key policy instrument. There has also been a general shift toward the adoption of inflation targets and the use of monetary policy to target inflation. This paper considers the significance of this shift in the emphasis of monetary policy, questions its effectiveness, and explores the role of fiscal policy. We examine these subjects from the point of view of the new consensus in monetary economics and suggest that its analysis is rather limited. When the analysis is broadened to embrace empirical issues and evidence, the conclusion clearly emerges that monetary policy is relatively impotent. We argue that fiscal policy (under specified conditions) remains a powerful tool for macroeconomic policy, particularly under current economic conditions.
Keywords: 330